Analisis Dampak Return On Invesment (ROI) dan Struktur Modal terhadap Price To Book Value (PBV): (Studi Pada Perusahaan Food and Beverage di BEI) - M. Sholihun (Al-Iqtishod : Jurnal Ekonomi Syariah, 2019)
This study is about financial analysis generally, it is incluiding how efficient the level of from firms operation is, what is the financial conditions and how hight of capital value as description of stock value for investor to take decision in investing their capital, especially in food and baverage firms. The statement of the problems in this study: are there any return in investing effect and structure of finances capital to price to book value in food and baverage firms, and which componens are more dominant in its effect between return on investment and finances firms structure to price to book value in food and bavarage firms. In this study, the researcher use Quantitative research which the population is all food and baverage firms that registered in Indonesian Stock Exchange, this study also used purposive sampling with 17 factories of food and baverage since 2003 till 2005. The data obtained by using scunder data with documentation technique. For analyzing used multiple analysis regrassion statistic linier. The result of study shows that there are significant effect between free variable, return on investment and capital structure, and bound variable, price to book value with 30,5 % contribution. The dominant effect between both return on investment and capital structure to price to book value is return on investment sith regression coefficient of 5,258. consequently, the investors are more interest to invest their capitals to return on investment than capital structure.